Linnaeocaninella nomen novum for the Middle Permian fossil Caninella Liang, 1990 (Brachiopoda: Productida: Richthofenidae), preoccupied by Caninella Gorsky, 1938 (Cnidaria: Anthozoa: Bothrophyllidae) - Hernández, José Amet Rivaz (Zootaxa, 2020)
Liang (1990) erected the monospecific genus Caninella for a Middle Permian fossil brachiopod species, Caninella zhinanensis, from the Lengwu Formation, Tonglu, Zhejiang, in China. This genus was included within the family Richthofenidae Waagen, 1885. Thus, Caninella zhinanensis, Liang, 1990, collected in strata of Middle Permian (Capitanian) age, was the type species by monotypy. Subsequently, Williams, Harper & Grant (2000) placed Caninella Liang, 1990 in the superfamily Permianelloidea, family Uncertain, subfamily Loczyellinae, but expressed doubt about the validity of Caninella since it was based on three poorly preserved specimens. Nevertheless, Shen et al. (2017) retain the placement in Richthofenidae on the basis of its somewhat bilobate outline and deep incisive sulcus in anterior or posterior views, but suggest that the genus is “highly likely a subjective synonym of either Richthofenia Kayser, 1881 or Permianella He & Zhu, 1979”.